The morphological and molecular variation of southern African Nannocharax (Characiformes: Distichodontidae), and its taxonomic implications - Smith, Timothy (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2019)
Nannocharax is the most species rich genus in the family Distichodontidae, being currently represented by 41 species. The genus is widely distributed across much of sub-Saharan Africa, with a range extending from the Zambezi ichthyofaunal province in the south to the Nilo-Sudan ichthyofaunal province in the north. In southern Africa, the genus is currently represented by four species, Nannocharax dageti Jerep, Vari, & Vreven, 2014, N. machadoi (Poll, 1967), N. macropterus Pellegrin, 1926, and N. multifasciatus Boulenger, 1923. Each of these species exhibit considerable intraspecific pigmentation pattern variation across their respective distribution ranges, suggesting that the current taxonomy possibly underestimates the taxonomic diversity of Nannocharax species in southern Africa. Much pigmentation pattern variation within these southern African species has been observed by both collectors and scientists in the field, prompting an investigation into the extent of this morphological variation as well as what molecular variation may occur as well. The genus displays a high degree of morphological conservatisim, making it difficult to assign external morphological characters as diagnostic. To this end, this study was conducted to determine the extent of diversity of this genus in the region, employing an integrative approach with traditional morphological analysis techniques as well as sequencing the 'barcoding gene', cytochrome oxidase I, testing the hypothesis that there is a greater, hidden diversity of this genus in the region than currently recognised. This study aims to identify these potential lineages and accurately map their distributions. Phylogenetic analyses were performed using maximum parsimony, maximum likelihood, and Bayesian inference, using the mitochondrial cytochrome oxidase I gene region. Massive genetic divergence was detected between populations of taxa previously considered to be singular, widely distributed species. The three approaches of phylogenetic inference used in this study yielded trees of comparable overall topology, with the exception of the maximum parsimony tree which indicated additional lineages within the southern African N. multifasciatus group. These analyses revealed four deeply divergent (1.3 "“ 12.3%) lineages within southern African N. macropterus, as well as two deeply divergent (0.4-14.6%) populations from the Congo ichthyofaunal region, the lineages here named "N. macropterus Congo 1" and "N. macropterus Congo 2" . Within the southern African region, two deeply divergent (10.3%) lineages of N. macropterus were identified from the Okavango River system, identified as "N. macropterus Okavango 2" lineage restricted to the Cuito-Canavale tributary, and "N. macropterus Okavango 1" distributed throughout the remainder of the Okavango system. "N. macropterus Okavango 2" shares a closer relationship with the unique lineage from the Kwanza ichthyofaunal region, named N. macropterus "Kwanza" , which itself is deeply divergent from the N. macropterus "Okavango 1" , N. macropterus "Zambezi" , N. macropterus "Congo 1" and N. macropterus "Congo 2" lineages (3.1-14.4%). Principal component analyses (PCA) and discriminant function analyses (DFA) produced overlapping clusters for all identified lineages, with the exception of the N. macropterus "Kwanza" lineage, which in all analyses clustered away from the other lineages. Analysis of variance (ANOVA) and Kruskall-Wallis tests indicated significant differences in means between character traits between lineages, however, overlap in measurements and counts occurred in all instances except between the N. macropterus "Kwanza" and N. macropterus Congo lineages. However the N. macropterus "Kwanza" lineages could be distinguished from the other lineages by generally smaller fin lengths (dorsal fin 19.5%SL vs 20.0-22.1%SL in others; pectoral fin 16.5%SL vs 20.6-21.8%SL in others; pelvic fin 18.3%SL vs 21.3-22.4) and pigmentation pattern differences. The N. macropterus species group displayed extensive pigmentation pattern variation, to the extent that five pattern grades could be used to classify them. These pattern grades, while not specific to river systems, showed patterns similar to that which was seen in the molecular analyses and could be linked to lineages with only minor overlap between them. Three lineages of N. multifasciatus were identified, with two occurring in the southern African region, each corresponding to a river system, being the N. multifasciatus "Zambezi" and N. multifasciatus "Okavango" lineages. This species group displayed shallower divergence between lineages than did the N. macropterus group, at 2.5% genetic distance. Genetic analysis inferred a closer relationship between the N. multifasciatus "Zambezi" and N. multifasciatus "Congo" lineages than with the N. multifasciatus "Okavango" lineage. Morphological PCA and DFA analyses indicated morphological divergence of the N. multifasciatus "Congo" lineage, with generally larger proportional measurements than southern African specimens (body width 12.6%SL vs 9.5-9.7%SL; body depth 26.6%SL vs 21.6-21.9%SL; head width 12.0%SL vs 10.0-10.4%SL). PCA, DFA, and measurements show a near complete overlap between the N. multifasciatus "Okavango" and N. multifasciatus "Zambezi" lineages. Pigmentation pattern variation occurred within this group, but none that could be assigned to a particular lineage. The N. machadoi species group in southern Africa consists of five lineages: N. machadoi "Zambezi 1" , N. machadoi "Zambezi 2" , N. machadoi "Kafue 1" , N. machadoi "Kafue 2" , and N. machadoi "Okavango" . This group displayed shallower genetic divergence between lineages than the other southern African Nannocharax species groups (0.4-1.3%). This shallow genetic divergence is paralleled by near complete morphological overlap, with PCA and DFA producing overlapping clusters, and measurements, meristics, and pigmentation pattern metrics consisting of very similar values for the lineages. These results indicate that what is considered to be "N. macropterus" in southern Africa should not be named as such. The N. macropterus "Zambezi" and the N. macropterus "Okavango 1" lineages, are misidentifications of Nannocharax dageti. Other "N. macropterus" from the southern African region possesses fewer circumpeduncular scales than the true N. macropterus as described by Pellegrin (1926), and require taxonomic re-evaluation, each here being recognised as a unique lineage with species status, here named N. macropterus "Okavango 2" and N. macropterus "Kwanza" . In particular, N. macropterus "Kwanza" displays deep genetic divergence as well as morphological dissimilarity with the other southern African "N. macropterus" groups. Nannocharax fasciolaris and N. monardi are here placed as junior synonyms of N. multifasciatus, owing to vast overlaps in measurements and character counts of these species and N. multifasciatus, which is also known to occur within the same geographical distribution, as well as dubious arguments from the original publications in delineating these species from N. multifasciatus. Therefore, there is insufficient evidence indicating the presence of multiple species originating from the Okavango system, where it is here indicated that only a single lineage of banded, adipose fin-bearing Nannocharax occurs, namely N. multifasciatus "Okavango" .
Keywords: Nannocharax -- Africa, Southern; Distichodontidae -- Africa, Southern; Freshwater fishes -- Africa, Southern; Nannocharax -- Genetics -- Africa, Southern; Distichodontidae -- Genetics -- Africa, Southern; Freshwater fishes -- Genetics -- Africa, Southern